2016
DOI: 10.1038/ncomms11416
|View full text |Cite
|
Sign up to set email alerts
|

Trapping mammalian protein complexes in viral particles

Abstract: Cell lysis is an inevitable step in classical mass spectrometry-based strategies to analyse protein complexes. Complementary lysis conditions, in situ cross-linking strategies and proximal labelling techniques are currently used to reduce lysis effects on the protein complex. We have developed Virotrap, a viral particle sorting approach that obviates the need for cell homogenization and preserves the protein complexes during purification. By fusing a bait protein to the HIV-1 GAG protein, we show that interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 41 publications
1
79
0
Order By: Relevance
“…The development of techniques such as BioID and Virotrap (partially) alleviated these shortcomings by means of covalent modification and avoiding cell lysis, respectively [91,97]. More specifically, BioID on the one hand takes advantage of marking PPIs by means of the covalent attachment of biotin, a stable modification that is retained during cell lysis conditions, opposed to the necessity for the maintenance of interactions upon cell lysis in case of AP-MS analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The development of techniques such as BioID and Virotrap (partially) alleviated these shortcomings by means of covalent modification and avoiding cell lysis, respectively [91,97]. More specifically, BioID on the one hand takes advantage of marking PPIs by means of the covalent attachment of biotin, a stable modification that is retained during cell lysis conditions, opposed to the necessity for the maintenance of interactions upon cell lysis in case of AP-MS analysis.…”
Section: Discussionmentioning
confidence: 99%
“…False positive interactions with GAG can be eliminated by comparing to a control setup. An appropriate VLP control setup, i.e., a representation of the complete VLP proteome in absence of the effector, is indispensable for Virotrap MS-based analysis as VLPs exhibit their own characteristic proteome content [97]. In the context of appropriate BioID controls, it is noteworthy that by using the power of genome editing, Vandemoortele et al designed a method to obtain isogenic cell lines expressing T2A-BirA* bait fusion or its corresponding BirA* control protein, both under the control of the endogenous bait promoter [105].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional studies illustrate that targeting the interaction between E2 and other identified host cellular proteins could be an efficient therapeutic strategy to eliminate persistent infection [ 47 , 48 , 64 , 65 , 66 ], providing a framework with which to approach developing HPV-specific therapeutics. Highly specific visualization/detection techniques such as bimolecular fluorescence complementation and Mammalian Protein–Protein Interaction Trap (MAPPIT) will likewise prove integral to identifying these synthetic and naturally occurring small molecule inhibitors [ 57 , 90 , 91 , 92 ].…”
Section: Current Therapeutic Strategies For Clearing Persistent Hpmentioning
confidence: 99%